PARADIGMA PENDIDIKAN KRITIS PAULO FREIRE DAN RELEVANSINYA DALAM PENGEMBANGAN PENDIDIKAN HUMANIS DI INDONESIA - Siswadi, Gede Agus (JAPAM (Jurnal Pendidikan Agama), 2024)
Education is the main sector in human resource development. So that education becomes an important part of human life. Through education humans can also find identity, hone potential, and improve the quality of life. This is inseparable from human desires that are free and independent in determining what kind of education they need. However, this seems to be a paradox by looking at the educational phenomenon which actually hinders the potential possessed by students with various dehumanization practices. Therefore, this study traces the thoughts of Paulo Freire with the idea of ​​critical education. The method used in this study is a qualitative method with a philosophical hermeneutic approach. The results of this study indicate that Paulo Freire is a critical education figure, who succeeded in dismantling the conventional educational model which tends to dehumanize. Conventional education actually views students as passive objects, each empty and must be regulated. Freire calls it the banking of education system. Notes from Freire's thoughts can be used as a reference in developing a humanist education system in Indonesia, namely by prioritizing students as the center of learning and recognizing students have diverse characters and potential. A teacher in humanist education acts as a facilitator by guiding students to be themselves.